(untitled) (Світ фінансів, 2017)
Колісник О. Я. Асиметрія територіального розвитку і міжбюджетні відносини: вплив на стан бюджетної безпеки України. Розглянуто проблеми розвитку міжбюджетних відносин в Україні у контексті ідентифікації загроз бюджетній безпеці держави. Проаналізовано тенденції асиметрії територіального економічного розвитку. Визначено напрямки модернізації бюджетної системи країни. Kolisnyk O. Asymmetry of territorial development and interbudgetary relations: infl uence on the state of budgetary safety of Ukraine. The problems of development of interbudgetary relations in Ukraine in the authentication context of threats to budgetary safety of the state are considered. The tendencies of asymmetry of territorial economic development are analysed. Directions of modernization of the country budgetary system are defi nite.